Perlindungan Hukum pada Tindak Pidana E-Commerce - Dewi Setyowati; Candra Pratama Putra; Ramdhan Dwi Saputro (Perspektif Hukum, 2018)
In executing a transaction to buy goods or services online, are required to be clear that the information will not cause consumers to lose. In terms of protecting the consumer, in Act No. 8 of 1999 on Consumer Protection, hereinafter called the Consumer Protection Act are one of the rights that are consumers, namely the right to correct information, clear and honest about the condition and guarantee of the goods and / or services , Then the rights for compensation, restitution and / or compensation, if the goods and / or services received are not in accordance with the agreement or not as it should be. This paper raises issues about how the legal protection of fraud in electronic commerce(e-commerce).The author will describe the victim in electronic commerce according to the study of victimology, the obligation of businesses on the products that will be offered electronically, protection of consumer rights in the conduct of electronic transactions and witnesses of crime that can catch the perpetrators of fraud in electronic transactions. Be consumers must be careful in making transactions although there has been a real UU ITE greatly assist consumers in electronic transactions and utilization activities in the field of information technology and telecommunications (ICT). Previously this sector has no legal basis, but is now increasingly clear that other forms of electronic transactions can now be used as a legitimate electronic evidence.